The shifting reasons for Beveridge-curve shifts - Gadi Barlevy; R. Jason Faberman; Bart Hobijn; Ayşegül Şahin (Federal Reserve Bank of Chicago, 2023)
We discuss how the relative importance of factors that contribute to movements of the U.S. Beveridge curve has changed from 1960 to 2023. We review these factors in the context of a simple flow analogy used to capture the main insights of search and matching theories of the labor market. Changes in inflow rates, related to demographics, accounted for Beveridge curve shifts between 1960 and 2000. A reduction in matching efficiency, that depressed unemployment outflows, shifted the curve outwards in the wake of the Great Recession. In contrast, the most recent shifts in the Beveridge curve appear driven by changes in the eagerness of workers to switch jobs. We argue that, while the Beveridge curve is a useful tool for relating unemployment and vacancies to inflation, the link between these labor market indicators and inflation depends on whether and why the Beveridge curve shifted. Therefore, a careful examination of the factors underlying movements in the Beveridge curve is essential for drawing policy conclusions from the joint behavior of unemployment and job openings.
Keywords: E52; J6; J20; 330; Beveridge curve; inflation; job openings; unemployment